PENGEMBANGAN MULTIMEDIA INTERAKTIF “BATUMBUH” PADA MATERI BAGIAN TUMBUHAN MATA PELAJARAN IPAS UNTUK SISWA KELAS IV SDN BULUSARI 3 - Astin Hadiahti Aulia; Bagus Amirul Mukmin; Farida Nurlaila Zunaidah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the low learning outcomes, understanding, and learning motivation of grade IV students of SDN Bulusari 3 on plant material due to the use of less varied learning media and teachers still use lecture methods in learning. To overcome this, an interactive multimedia learning media "BATUMBUH" was developed. This study aims to determine the validity, practicality, and effectiveness of the media using the ADDIE Research and Development model. The results of the study showed that (1) the validity of the interactive multimedia "BATUMBUH" plant part material obtained an average score percentage of 93% with very valid and very good use criteria, (2) the practicality of obtaining the average percentage result was 92.25% with very practical criteria, (3) the effectiveness of obtaining the average percentage of score is 100%, the result is declared to be very effective. Thus, it can be concluded that the interactive multimedia "BATUMBUH" plant part material is very valid, very practical, and very effective to be implemented in the learning process.